The Depth-Depended Fungal Diversity and Non-depth-Depended Aroma Profiles of Pit Mud for Strong-Flavor Baijiu - Cai, Wenchao; Xue, Yu’ang; Tang, Fengxian; Wang, Yurong; Yang, Shaoyong; Liu, Wenhui; Hou, Qiangchuan; Yang, Xinquan; Guo, Zhuang; Shan, Chunhui (Frontiers in Microbiology, 2022)
Microorganisms in pit mud are the essential factor determining the style of strong flavor Baijiu. The spatial distribution characteristics of fungal microorganisms and aroma in the pit mud for strong flavor Baijiu with normal fermentation of Xinjiang, China were investigated using Illumina MiSeq high-throughput sequencing and electronic nose technology. A total of 138 fungal genera affiliated with 10 fungal phyla were identified from 27 pit mud samples, of which Saccharomycopsis, Aspergillus, and Apiotrichum were the core fungal communities, and Aspergillus and Apiotrichum were the hubs that maintain the structural stability of fungal communities in pit mud. The fungal richness and diversity as well as aroma of pit mud showed no significant spatial heterogeneity, but divergences in pit mud at different depths were mainly in pH, total acid, and high abundance fungi. Moisture, NH4+, and lactate were the main physicochemical factors involved in the maintenance of fungal stability and quality in pit mud, whereas pH had only a weak effect on fungi in pit mud. In addition, fungal communities were not significantly associated with aroma of pit mud. The results of this study provide a foundation for exploring the functional microorganisms and dissecting the brewing mechanism of strong flavor Baijiu in Xinjiang, and also contributes to the improvement of pit mud quality by bioaugmentation and controlling environmental physicochemical factors.